흡연환자의 효과적인 금연정책에 대한 연구 - 황지민; Ji Min Hwang; 김응권; Eung Gwon Kim; 박용덕; Yong Duk Park; 한지형; Ji Hyoung Han (Chiwisaeng gwahakoeji, 2013)
The purpose of this study was to examine the subjective awareness of smoker patients about the preparation of smoking cessation plans in an effort to lay the foundation for smoking cessation policy setting. The subjects were the selected patients at a dental clinic. A self-administered survey was conducted to grasp their personal characteristics, and the selected answer sheets from 236 respondents were analyzed. The findings of the study were as follows: 1. As for the extension of existing smoking cessation plans, the largest group (32.6%) preferred smoking cessation education, followed by smoking cessation counseling (28.8%), prescription of an smoking cessation aid (18.6%). 2. Concerning the necessity of a smoking cessation law, the men and the women respectively gave 2.37 and 3.00 to that, and the gender gap was significant. The patients had a significantly different opinion on the necessity of a rise in tobacco price according to their occupation and monthly mean household income, and their took a significantly different view of the necessity of smoking cessation counseling according to their residential area. 3. As a result of analyzing the correlation between their on effective smoking cessation policies and the related variables, all the variables had a statistically significant correlation to each other. 4. As a result of analyzing their opinions on what institution should be in charge of smoking cessation plans, the biggest group answered that dental clinics should be responsible for smoking cessation-aid prescription (50.0%), and the largest group replied that smoking cessation education and smoking cessation counseling should respectively be provided by public dental clinics (37.3%) and dental clinics (44.1%).The above-mentioned findings suggest that the preparation of new smoking cessation measures and the extension of existing smoking cessation plans are urgently required, and that dentists and dental hygienists should make a concerted effort to offer counseling and education to stimulate dental patients to abstain from smoking.